2014
DOI: 10.12954/pi.14059
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between visual prostate symptom score and international prostate symptom score in males older than 40 years in rural Indonesia

Abstract: PurposeTo evaluate the effect of education and literacy status on completion of the Visual Prostate Symptom Score (VPSS) and the International Prostate Symptom Score (IPSS) in males aged over 40 years in a rural Indonesian area.MethodsWe enrolled 103 men who had visited Tc-Hillers Maumere Hospital. Four questions related to frequency, nocturia, weak stream, and quality of life (QoL) were presented by pictogram in the VPSS. Data on age, educational level, and literacy status were analyzed to determine associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
2
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 15 publications
4
19
2
6
Order By: Relevance
“…Construction of the intuitive visual analog scale ( VAS ) - based questionnaires are much preferable as such questionnaires have no significant differences with those, text-based, like IPSS [ 137 ].…”
Section: Discussionmentioning
confidence: 99%
“…Construction of the intuitive visual analog scale ( VAS ) - based questionnaires are much preferable as such questionnaires have no significant differences with those, text-based, like IPSS [ 137 ].…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of the correlations in this study is similar to that reported by van der Walt et al (r = 0.64, p<0.001) and Afriansyah et al (r = +0.675, p <0.001). 11,17 The statistically significant positive correlations between the total scores and the QoL scores reported in this study was stronger for the VPSS (r = +0.898) than the IPSS (r = +0.589) probably because more patients were able to complete the VPSS without physician assistance thereby minimizing bias. These findings indicate that the VPSS can be reliably used in place of the IPSS to subjectively assess the severity of LUTS in men with symptomatic BPE.…”
Section: Discussionmentioning
confidence: 66%
“…The results are consistent with the study done by van der walt and others. [13][14][15][16] Another study comparing IPSS and VPSS in patients with urethral stricture disease also shows similar positive correlation. Similarly, specific questions of IPSS related to frequency, nocturia and weak stream have also been positively correlated with the respective components in VPSS.…”
Section: 20mentioning
confidence: 63%
“…13 This is easy to use and comprehend even by patients with lower education level. [14][15][16] It is simple, easily completed without assistance and less time taking.…”
Section: Jssn 2015; 18 (2)mentioning
confidence: 99%